Effect of UiO-66 NH2 on hydrogen storage performance of MgH2 - Siti Nurqurratulainie, Miskan; Abdulkadir, Bashir Abubakar; Muhammad, Ismail; Herma Dina, Setiabudi (Elsevier, 2026)
In this study, UiO-66-NH2, known for its excellent thermal stability, was incorporated into MgH2 for the first time, demonstrating strong catalytic activity in enhancing the hydrogen storage performance of MgH2. The effects of varying UiO-66-NH2 loadings (5, 10, 15, and 20 wt%) on the hydrogen storage behavior of MgH2 were systematically examined using a ball milling process. The introduction of UiO-66-NH2 significantly lowered the onset desorption temperature from 350 °C (for milled MgH2) to 280 °C. The composite exhibited markedly improved kinetics, achieving rapid hydrogen absorption of approximately 6.2 wt% within 2 min at 250 °C under 33.0 atm H2 pressure, and desorption of about 5.9 wt% within 2 min. The apparent activation energy for dehydrogenation decreased to 89.17 ± 3.2 kJ/mol H2, compared to 132 ± 8.7 kJ/mol H2 for pure MgH2. The MgH2/UiO-66-NH2 composite maintained excellent cyclic stability over 20 cycles, with only a minor capacity loss of about 0.002 wt%. Comprehensive characterization using XRD, TEM, and SEM confirmed the structural and morphological changes, and a plausible catalytic mechanism of UiO-66-NH2 on MgH2 was proposed based on these findings.